Exploring Court Systems in the Region: The Case of Indonesia - Shuaib, Farid Sufian (2012)
The court is the main dispute resolution mechanism, apart from mediation and arbitration. In conducting business and other human interactions, disputes could not be altogether avoided. Thus, it is important to build up knowledge about court systems in the region. In this exploratory study, the objective is to examine the set up of the court systems in the region and the first step is to look at Indonesia who has posted a 6.5% rise in gross domestic product last year with a population of 240 million and she received US$19.3 billion foreign direct investment in 2011, compared with US$17 billion the year before. The exploratory research will look at the relevant laws and writings on the Indonesian court system. The position of the Religious Court with regard to its final reference to the Supreme Court and inclusion of ekonomi Islam under its jurisdiction are among matters that Malaysia could study further.